2020
DOI: 10.3389/fvets.2020.00435
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Porcine Epidemic Diarrhea Virus With a Naturally Occurring Truncated ORF3 Gene Found in Guangxi, China

Abstract: Porcine epidemic diarrhea virus (PEDV) is one of the major enteric pathogens, causing severe enteric disease, resulting in enormous economic losses. The ORF3 gene encodes an accessory protein which is related to the infectivity and virulence of PEDV. In this study, 33 PEDV positive field samples were collected from Guangxi, from 2017 to 2019, and the genetic diversity of ORF3 was investigated. Thirty-eight strains of ORF3 were obtained, and these were composed of five strains of ORF3 named Guangxi naturally tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The ORF3 protein of the HLJBY strain only consists of 91 aa, with 133 aa deletions at the C’ end [ 24 ]. Recently, we discovered a new ORF3 genotype that encoded a truncated protein of 89 aa, with continuous deletions from 172–554 bp [ 25 ]. However, no co-infection of multiple ORF3 genotypes has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ORF3 protein of the HLJBY strain only consists of 91 aa, with 133 aa deletions at the C’ end [ 24 ]. Recently, we discovered a new ORF3 genotype that encoded a truncated protein of 89 aa, with continuous deletions from 172–554 bp [ 25 ]. However, no co-infection of multiple ORF3 genotypes has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…PEDV ORF3 deletion strains have been reported in China [ 24 ]. In our previous work, we found that two ORF3 genotypes were present in the same piglet, one of which had a naturally truncated ORF3 gene that contained a continuous 382 nucleotides deletion from 172–554 bp, and the other of which had an intact ORF3 gene of 675 nucleotides [ 25 ]. Thus, we suspected that a co-infection with two different PEDV strains occurred in the piglet.…”
Section: Introductionmentioning
confidence: 99%
“…recombination or accumulation of point mutations, which can result in the virus losing its antigenicity and even the vaccine failing to work [33][34][35]. The molecular characterization of PEDVs is a major focus of swine diarrhea virus research due to the virus's high prevalence.…”
Section: Plos Onementioning
confidence: 99%
“…The primers have been described previously with some of modifications (10) (Table 1). The viral genomic RNA was extracted from the EV-G stock samples using the Axy Prep TM Viral DNA/RNA Miniprep Kit (OMEGA, USA) according to the manufacturer's instructions (31). The cDNA was synthesized in a total volume of 25 µL containing 16 µL of RNA solution, 2 µL of dNTP mixture, 0.5 µL of reverse transcriptase M-MLV, 0.5 µL of RNasin inhibitor, 1 µL of oligo (dT) or the reverse primer, and 5 µL of 5× reverse transcriptase M-MLV buffer.…”
Section: Sequencing and Data Analysismentioning
confidence: 99%